2022
DOI: 10.3354/meps13946
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional migrations from a major nesting area in Turkey support the widespread distribution of foraging sites for loggerhead turtles in the Mediterranean

Abstract: Satellite tracking studies have identified some of the migratory corridors and foraging sites of Mediterranean loggerhead sea turtle (Caretta caretta) rookeries over the past few decades. However, due to a lack of information for breeding rookeries in Libya and Turkey, our understanding of the distribution and connectivity of adult loggerheads is limited. We satellite-tracked 17 female loggerhead turtles breeding in one of the main nesting areas in Turkey to identify (1) migratory pathways, and (2) their forag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Previous studies suggested that adult loggerheads in the Mediterranean Sea inhabit foraging grounds usually hosted at the neritic zone (Wallace et al 2011, Zbinden et al 2008, 2011, Casale et al 2013, Luschi et al 2013, Mingozzi et al 2016, Snape et al 2016, Almpanidou et al 2022, and exhibit smaller home ranges than those turtle life stages that inhabit oceanic habitats (Schofield et al 2010, Snape et al 2016. However, recent studies suggested that adult turtles in the Mediterranean may alternate between neritic and oceanic habitats due to the short distance between the two types of habitat in the Mediterranean basin (Ten et al 2019, Cerritelli et al 2022, Baldi et al 2023.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that adult loggerheads in the Mediterranean Sea inhabit foraging grounds usually hosted at the neritic zone (Wallace et al 2011, Zbinden et al 2008, 2011, Casale et al 2013, Luschi et al 2013, Mingozzi et al 2016, Snape et al 2016, Almpanidou et al 2022, and exhibit smaller home ranges than those turtle life stages that inhabit oceanic habitats (Schofield et al 2010, Snape et al 2016. However, recent studies suggested that adult turtles in the Mediterranean may alternate between neritic and oceanic habitats due to the short distance between the two types of habitat in the Mediterranean basin (Ten et al 2019, Cerritelli et al 2022, Baldi et al 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Only one female (turtle ID Victoria), which was satellite-tracked more than 2 years (and counting), frequented neritic foraging grounds for a 3-month period at the Tunisian Plateau and Libyan coastal waters before returning to the western basin, suggesting that this foraging area is used by females nesting on the western basin. The Tunisian Plateau and the coast of Libya are known foraging grounds for adult loggerhead turtles from other Mediterranean regions (see Mingozzi et al 2016, Levy et al 2017, Almpanidou et al 2022, Cerritelli et al 2022). This result supports previous studies in which adult individuals from a given breeding rookery might use different foraging grounds, often separated by hundreds of kilometres (Bentivegna 2002, Zbinden et al 2008, Schofield et al 2010a, Schofield et al 2013.…”
Section: Discussionmentioning
confidence: 99%